2020
DOI: 10.4314/ijbcs.v14i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Mesures des indicateurs de prolifération des larves de moustiques au niveau des mares permanentes et semi permanentes de Saga, Niger

Abstract: Les Culicidae, communément appelés moustiques, par leur large distribution et leur abondance, sont impliqués dans la transmission de nombreuses maladies humaines et animales. La lutte contre ces insectes nécessite la connaissance de leurs lieux de développement dans lequel évoluent les stades pré imaginaux. La présente étude vise à caractériser ces gîtes larvaires en vue d’identifier les indicateurs entomologiques et écologiques de production de larves dans ces milieux. Pour ce faire, le pH, la température, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The presence of mosquito species in Reghaia lake is the result of several factors including physicochemical parameters. The temperature, pH, salinity, and dissolved oxygen recorded during the present study are favorable for the development of several species of mosquitoes as mentioned by several authors (El Ouali Lalami et al, 2010;Ibrahim et al, 2011;Marc et al, 2016;Iro et al, 2020).…”
Section: Resultssupporting
confidence: 78%
“…The presence of mosquito species in Reghaia lake is the result of several factors including physicochemical parameters. The temperature, pH, salinity, and dissolved oxygen recorded during the present study are favorable for the development of several species of mosquitoes as mentioned by several authors (El Ouali Lalami et al, 2010;Ibrahim et al, 2011;Marc et al, 2016;Iro et al, 2020).…”
Section: Resultssupporting
confidence: 78%
“…pipens present in sites with high conductivity and low levels of dissolved oxygen. 47 Culiseta longiareolata was observed to grow in different types of environments. 40,48 In the present study, it was observed to be dominant in permanent and shallow breeding sites.…”
Section: Resultsmentioning
confidence: 99%
“…Larval surveys conducted during this study showed a high diversity of larval breeding sites colonized by Aedes aegypti larvae. The majority of these were created by man (Iro et al, 2020) because of his activities as observed by Tia et al (2016) and Koumba et al (2018). Thus, the classification of the larval sites inventoried made it possible to observe that the breeding places of mosquitoes of the genus Aedes and especially Aedes aegypti in households in Abidjan were made up of water storage containers and abandoned containers.…”
Section: Discussionmentioning
confidence: 99%